Market sidedness: Insights into motives for trade initiation - Asani Sarkar; Robert A. Schwartz (Federal Reserve Bank of New York, 2007)
In this paper, we infer motives for trade initiation from market sidedness. We define trading as more two-sided (one-sided) if the correlation between the numbers of buyerand seller-initiated trades increases (decreases), and assess changes in sidedness (relative to a control sample) around events that identify trade initiators. Consistent with asymmetric information, trading is more one-sided prior to merger news. Consistent with belief heterogeneity, trading is more two-sided (1) before earnings and macro announcements with greater dispersions of analyst forecasts and (2) after earnings and macro news events with larger announcement surprises. A simultaneous equation system is used to examine the co-determinacy of sidedness, the bid-ask spread, volatility, the number of trades, and the order imbalance.
Keywords: G10; G14; G34; 330; sidedness; divergent beliefs; trade initiation; trading motives; earnings news; macro news; Ankündigungseffekt; Wertpapierhandel; Aktienmarkt; Marktmechanismus; USA